Love is heterosexual‐by‐default: Cultural heterosexism in default prototypes of romantic love. (2nd October 2020) - Thorne, Sapphira R.; Hegarty, Peter; Hepper, Erica G.
Abstract : Cultural heterosexist ideologies assume heterosexuality to be the default norm. Four studies investigated when concepts of romantic love are heterosexual‐by‐default ( N = 685). In Studies 1–2, participants generated features of romantic love, in general (i.e., the default prototype) or among one of three sexual orientation‐specific couples (lesbian, gay, or heterosexual). Heterosexual‐identified participants' default prototypes were more similar to heterosexual than same‐gender prototypes (Study 1). Lesbian‐ and gay‐identified participants' default prototypes were more similar to both heterosexual and gay male than lesbian prototypes, whereas bisexual‐identified participants' sexual orientation‐specific prototypes were equivalently similar to the default (Study 2). However, heterosexual‐identified participants rated presented features of love similarly across sexual orientation‐specific conditions (Study 3). In a timed feature‐verification task (Study 4), participants categorized fewer peripheral features of romantic love as relevant to same‐gender than mixed‐gender couples. Activating sexual orientation‐specific representations affected subsequent default concepts of romantic love. We discuss implications for heterosexism theories and intervention.